2016
DOI: 10.1002/pon.4065
|View full text |Cite
|
Sign up to set email alerts
|

Linking dispositional mindfulness and positive psychological processes in cancer survivorship: a multivariate path analytic test of the mindfulness-to-meaning theory

Abstract: Background Research indicates that dispositional mindfulness is associated with positive psychological functioning. Although this disposition has been linked with beneficial outcomes in the broader mental health literature, less is known about dispositional mindfulness in cancer survivors and how it may be linked with indices of psychological and physical health relevant to cancer survivorship. Methods We conducted a multivariate path analysis of data from a heterogeneous sample of cancer patients (N = 97) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 26 publications
(33 reference statements)
9
53
2
1
Order By: Relevance
“…In a series of studies, Brown and Ryan [7] showed that dispositional mindfulness was negatively related to psychological symptoms such as anxiety, depression, hostility, and impulsivity. Similar results have been obtained from studies on cancer patients; those with higher levels of dispositional mindfulness showed a lower proclivity for emotional disturbances [6], and reported less sleeping problems [9]. In addition, mindfulness-based therapy, which takes dispositional mindfulness as the main target of improvement and development, is of great significance among different psycho-therapies proposed to improve mental health status in the field of psycho-oncology [10].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In a series of studies, Brown and Ryan [7] showed that dispositional mindfulness was negatively related to psychological symptoms such as anxiety, depression, hostility, and impulsivity. Similar results have been obtained from studies on cancer patients; those with higher levels of dispositional mindfulness showed a lower proclivity for emotional disturbances [6], and reported less sleeping problems [9]. In addition, mindfulness-based therapy, which takes dispositional mindfulness as the main target of improvement and development, is of great significance among different psycho-therapies proposed to improve mental health status in the field of psycho-oncology [10].…”
Section: Introductionsupporting
confidence: 71%
“…However, few studies to date have examined the mechanisms underlying the relationship between dispositional mindfulness and psychological symptoms except a small sample study [9] proposes that mindfulness can influence every stage of the stress process (e.g., appraisal, coping, emotional outcome, health outcome). Accordingly, mindfulness reduces the degree of stress individual perceived via the promotion of increased present awareness of, and productive responding to, potential stressors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Though often studied in relation to terminally ill patients, existential suffering also manifests in cancer survivorship . Psychosocial interventions to address existential suffering traditionally encompass, among others, coping strategies and mindfulness techniques . The human challenges of cancer carry serious underexposed side effects that though addressed by these well‐documented psychosocial interventions is philosophical in nature.…”
Section: Introductionmentioning
confidence: 99%
“…3 Psychosocial interventions to address existential suffering traditionally encompass, among others, coping strategies 4 and mindfulness techniques. 5 The human challenges of cancer carry serious underexposed side effects that though addressed by these well-documented psychosocial interventions is philosophical in nature. The existential concerns that are caused by the cancer experience go to the very subject matter of philosophy.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer rehabilitation, or restoring oneself post cancer, is a perpetual endeavor that calls on a host of psycho-social activities (Hopman et al, 2015;Park et al, 2008;Garland et al, 2016). Participation in a SDG does not offer assistance in returning to the job market or proposing coping strategies in treating mental stress and anxiety.…”
Section: The Potential Of Sdg In Cancer Survivor Carementioning
confidence: 99%